Xu Guangqiâ€™s Thought On Supplementing Confucianism With Christianity - Seo, Anna (Lingua Cultura, 2012)
Xu Guangqi is one of the most influential Chinese scholars who accepted Christian faithÂ during the late Ming dynasty. His idea of â€œsupplementing Confucianism and replacing Buddhism byÂ Christianityâ€ had great impact on the development of Christianity in China. His idea, however, hasÂ often been accused of syncretism, and genuineness of his Christian faith has been put into question.Â Some argue that his theology lacks Christology. Others suggest that his ultimate goal was to achieveÂ the Confucian political ideals through adopting some of the Christian moral teachings. Through theÂ analysis of Xu Guangqiâ€™ works and life, we find that he accepted all the essential Christian doctrinesÂ and Christology is the core of his understanding of â€œTianzhuâ€. His view on Confucianism itself istransformed through Christian perspective. In his new understanding, the ultimate goal ofÂ Confucianism is to serve and to worship â€œTianzhuâ€ï¼Œsame as Christianity. The ultimate problem of lifeÂ is to save oneâ€™s soul.Xu Guangqi considered his scientific works as a way to propagate Christian faith,since science was seen as an integral part of Christian thought and practice. His idea ofÂ â€œsupplementing Confucianism by Christianityâ€ integrated Confucianism into the overarchingÂ framework of Christian thought.